2003
DOI: 10.1046/j.1365-2362.2003.01221.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and interventional dietary study in humans on the role of HDL fatty acid composition in PGI2 release and Cox‐2 expression by VSMC

Abstract: Our results suggest that lipid moiety modulates HDL-induced PGI2 release/Cox-2 up-regulation in human VSMCs, and that changes in fatty acids as accomplished with the diet can modulate vascular PGI2 homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 63 publications
1
19
0
Order By: Relevance
“…The impact of HDL on prostacyclin production in endothelium occurs by both the provision of arachidonate ( 178,180,183 ) and upregulation of Cox-2 expression ( 184,185 ). It has also been observed that HDL3 induces Cox-2 expression and prostacyclin release via a p38 MAPK/CREB-dependent pathway in the endothelium (185)(186)(187)(188). Recently, it was demonstrated that apoA-I, but not apoA-II, induced the expression of Cox-2 and the production of prostacyclin through the p38 MAPK, ERK1/2, and JAK2 pathways via ABCA1 in endothelial cells ( 189 ).…”
Section: Effects Of Hdl On Endothelial Thrombotic Activationmentioning
confidence: 99%
“…The impact of HDL on prostacyclin production in endothelium occurs by both the provision of arachidonate ( 178,180,183 ) and upregulation of Cox-2 expression ( 184,185 ). It has also been observed that HDL3 induces Cox-2 expression and prostacyclin release via a p38 MAPK/CREB-dependent pathway in the endothelium (185)(186)(187)(188). Recently, it was demonstrated that apoA-I, but not apoA-II, induced the expression of Cox-2 and the production of prostacyclin through the p38 MAPK, ERK1/2, and JAK2 pathways via ABCA1 in endothelial cells ( 189 ).…”
Section: Effects Of Hdl On Endothelial Thrombotic Activationmentioning
confidence: 99%
“…COX-2 has commonly been associated with pro-infl ammatory/proatherogenic stages, due to its upregulation at infl ammatory sites such as active atherosclerotic lesions. However, COX-2 is constitutively expressed in the endothelium ( 13,14 ), is upregulated by atheroprotective lipoproteins in vascular cells (15)(16)(17), and seems to contribute to the innate defensive mechanism of the myocardium ( 18,19 ). Indeed, the pathophysiological meaning of COX-2 induction in a particular setting depends on the activity of downstream enzymes that transform PGH 2 into different prostanoids in a cell-type-specifi c manner ( 12,20 ).…”
Section: Cox and Pgis Enzymatic Activitiesmentioning
confidence: 99%
“…12 Moreover, HDL impedes vascular SMCs proliferation and S-phase entry, and this results from the upregulation of prostacyclin (PGI2) and cyclooxygenase-2 (COX-2) expression. 149,150 HDL has also been found to inhibit PDGFinduced migration of vascular SMCs, which is attributed to the S1P2 receptor-dependent manner. 151,152 Studies of vascular SMCs and rat aortic explants have revealed the HDL-dependent inhibition of MCP-1 production was accompanied by the suppression of ROS, which is associated with SR-BI and S1P3 receptor in vascular SMCs, suggesting inhibition of NAD(P) H oxidase activity by HDL-associated lysosphingolipids may constitute an important mechanism by which HDL exerts its potent antiatherogenic effects.…”
Section: Hdl Regulation Of Vsmc Proliferation and Migrationmentioning
confidence: 96%
“…Second, HDL inhibits inflammatory chemokine‐stimulated proliferation of SMCs, which may be related to the SR‐BI‐dependent deactivation of PI3K/AKT pathway . Moreover, HDL impedes vascular SMCs proliferation and S‐phase entry, and this results from the up‐regulation of prostacyclin (PGI2) and cyclooxygenase‐2 (COX‐2) expression . HDL has also been found to inhibit PDGF‐induced migration of vascular SMCs, which is attributed to the S1P2 receptor‐dependent manner .…”
Section: Potential Function Of Hdl In Antirestenosismentioning
confidence: 99%